Heart failure with preserved ejection fraction: Refocusing on diastole. (20th January 2015) - Abbate, Antonio; Arena, Ross; Abouzaki, Nayef; Van Tassell, Benjamin W.; Canada, Justin; Shah, Keyur; Biondi-Zoccai, Giuseppe; Voelkel, Norbert F.
Abstract: Heart failure (HF) with preserved ejection fraction (HFpEF) is a clinical syndrome of exercise intolerance and/or congestion, in the presence of a left ventricular (LV) ejection fraction within the normal limits (i.e. LVEF > 50%). Determining the presence of impaired LV relaxation and/or filling (diastolic dysfunction) in HFpEF is needed to pragmatically to distinguish it from other cardiac and non-cardiac conditions where symptoms are not due to HF. There are multiple mechanisms for diastolic dysfunction ranging from structural abnormalities to functional derangements in HFpEF yet tailored therapies are lacking. Treatments proven effective in HF with systolic dysfunction have failed to show significant benefit in patients with HFpEF, which prognosis remains poor. This review will discuss the challenges inherent to the use of diagnostic criteria for HFpEF, differential diagnosis, prognostic evaluation, and treatment, highlighting the need for more research in this field. Highlights: Heart failure (HF) is the only cardiac disease with an increasing incidence. HF is the final common presentation of a variety of cardiac diseases. 50% of patients with HF have no evidence of left ventricular systolic dysfunction. HF with preserved EF (HFpEF) refers primarily to the absence of systolic dysfunction. Diagnosis of HFpEF requires evidence of an abnormal diastolic function. It is necessary to differentiate HFpEF from other cardiac and non-cardiac conditions.